2008
DOI: 10.1159/000190403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Small Bowel Injury in Patients with Rheumatoid Arthritis by Capsule Endoscopy: Effects of Anti-Rheumatoid Arthritis Drugs

Abstract: Background and Aim: The medical treatment of rheumatoid arthritis (RA) includes nonsteroidal anti-inflammatory drugs (NSAIDs), low-dose corticosteroids, and disease-modifying antirheumatic drugs (DMARDs). We evaluated the incidence of small bowel injury in RA patients who were taking anti-RA drugs with or without concomitant NSAIDs by capsule endoscopy. Methods: A total of 28 RA patients who took low-dose corticosteroids and/or DMARDs for more than 1 year were enrolled. Results: The incidence of red spots did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 45 publications
0
49
1
2
Order By: Relevance
“…However, Maiden et al [71] recently found no difference in the incidence of small intestinal injury between chronic users of traditional NSAIDs and chronic users of selective COX-2 inhibitors. Furthermore, Sugimori et al [11] also found the incidence of mucosal breaks in chronic users of preferential COX-2 inhibitors (meloxicam and etodolac) was high, and similar to that in traditional NSAID users. Maiden [72] speculated the reasons as following.…”
Section: Prevention and Treatment Of Small Intestinal Mucosal Injury mentioning
confidence: 80%
See 1 more Smart Citation
“…However, Maiden et al [71] recently found no difference in the incidence of small intestinal injury between chronic users of traditional NSAIDs and chronic users of selective COX-2 inhibitors. Furthermore, Sugimori et al [11] also found the incidence of mucosal breaks in chronic users of preferential COX-2 inhibitors (meloxicam and etodolac) was high, and similar to that in traditional NSAID users. Maiden [72] speculated the reasons as following.…”
Section: Prevention and Treatment Of Small Intestinal Mucosal Injury mentioning
confidence: 80%
“…They reported a high incidence of smallintestinal mucosal injury at 71% after NSAID administration. In Japan, Sugimori et al [11] also performed VCE in 28 rheumatoid arthritis patients who had been using disease-modifying antirheumatic drugs or low-dose steroids for at least 1 year. They observed small bowel injuries in 13 of 16 patients (81.3%) who used NSAIDs and in 4 of 12 patients (33.3%) who did not.…”
Section: Present Status Of Small Intestinal Mucosal Injury Caused By mentioning
confidence: 99%
“…More bowel ulcerative lesions are expected in the elderly because their large [18] and small bowel [19] is more vulnerable to NSAIDs. Patients with rheumatic diseases were excluded because rheumatoid artritis can cause small bowel ulcerative lesions in the absence of NSAID consumption [20] . Rheumatoid arthritis has been related to an increased frequency of iron deficiency anemia [21] and small bowel ulcerative lesions [20] , among NSAIDs consumers, but no overt bleeding episodes [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with rheumatic diseases were excluded because rheumatoid artritis can cause small bowel ulcerative lesions in the absence of NSAID consumption [20] . Rheumatoid arthritis has been related to an increased frequency of iron deficiency anemia [21] and small bowel ulcerative lesions [20] , among NSAIDs consumers, but no overt bleeding episodes [21] . Sample size although marginally adequate to explore the role of…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel ulcers were observed in 8 % of NSAIDtreated patients in comparison to 0.6 % of controls (with no history of NSAID use) in a prospective, autopsy-based study (713 cases) (4). The endoscopically evident changes (including ulcers) were diagnosed by means of sonde or push enteroscopy in 41-66 % (62, 63, 64) and by means of capsule and double balloon enteroscopy in 16-88 % of NSAID users (30,32,36,59,60,81). Other tests of small bowel damage and malfunction (faecal occult blood test, assessment of intestinal inflammation and permeability) confirm NSAID-enteropathy in 19-72 % (7, 8, 9, 10, 11, 12, 56, 83).…”
mentioning
confidence: 99%